An Analysis of Sharia Economic Law on Takeover from Conventional Bank to Bank Syariah Mandiri Branch in Ciamis - Mustofa Mustofa (Jurnal Madania)
Bank Syariah Mandiri (BSM) branch (KCP) in Ciamis was very transparent in providing financing products, especially takeover services or the transfer of customer debt from conventional banks to BSM. This study aimed at analyzing the causes of takeover from conventional banks to Bank Syariah Mandiri and analyzing the law of take over. Current research was a qualitative research by using observation and interview techniques. The research process was employed naturally, towards direct observation and in-depth interview. Data obtained were analyzed by applying Miles and Huberman of flow models, includingcollecting, reducing, displaying the data, and drawing conclusions. The results of the study revealed that the causes of the takeover were BSM provided education to customers to transact according to Islamic economic principles; transactions free from usury that led to benefit, justice, and peace. BSM provided several services such as convenient requirements, no penalties, and cheap installments. Benefits and application of Islamic sharia consideration were depicted from findings. The services encouraged customers to perform takeover. However, in terms of Islamic economic law, transfer of customer debt from conventional banks to BSM KCP Ciamis was permitted. This was consistent to Q.S. Al-baqarah [2]: 245; ijmak scholars who agreed to allow the transfer of debt; and DSN fatwa suggested that syirkah al-milk, murabahah, qardh, ijarah muntahiya bi al-tamlik were sharia compliance and avoided from riba and gharar.